(887) Process Control Series: Equipment Specification سلسلة التحكم في العمليات: مواصفات المعدات - Al-Walid El- Shafei. (معهد التخطيط القومى, 2024)
This series of articles addressed the fundamental aspects of process control. The second article emphasized the role of Operations Research in studying and implementing process control. A case study in the iron and steel industry illustrated practical applications. A concise description of the software involved in the system was provided in the third article. The fifth article discussed the economic evaluation and justification of computer use in process control, with references to real-world cases. Finally, attention will be given to the specifications of process control equipment, focusing on performance, reliability, adequacy, durability, and how to make informed decisions about selecting the right equipment.